TEA Promoting employment and growth in rural India - Chimyang, Chamin; Tsomu, Thupten; Tangjang, Sumpam (Indian Farming, 2024)
Tea (Camellia sinensis (L.) Kuntze), commonly grown in the hilly tracts of Tirap district, Arunachal Pradesh, is a largely consumed local beverage. A large number of small tea growers’ sell the green leaf to the nearby tea factories which rather fetch a measly income to the household. This article thus, discusses the epicenter of commercial growth of Luthong village of the Tirap district that is making way to socio-economic growth of rural India via initiating a tea business. Additionally, it sheds light upon the minor horticultural crops and its nutraceutical properties that is blended with the tea leaves, serving as herbal product in the daily cup of tea.